Efficient hydrogen production from solar energy and fossil fuel via water-electrolysis and methane-steam-reforming hybridization. (15th October 2020) - Sui, Jiyuan; Chen, Zhennan; Wang, Chen; Wang, Yueyang; Liu, Jianhong; Li, Wenjia
Highlights: Full-spectrum solar H2 production with electro- and thermo-chemical hybridization. Photovoltaic-electrolysis & methane-steam-reforming is integrated by spectral splitting. Impact of wavelength on efficiency is studied to make full-spectrum use of sunlight. New system produces 4.2% more H2 and saves 3.8% fossil fuel than reference system. Efficient use of sunlight and low-carbon use of fossil fuel are reached synergistically. Abstract: A new concept of efficient and low-carbon hydrogen production via thermochemical and electrochemical hybrid route based on full-spectrum utilization of solar energy is proposed: sunlight with wavelength suitable for PV conversion is assigned to PV cells for electricity production, which drives water electrolysis for hydrogen production; the rest sunlight is assigned to thermal collectors and utilized for thermochemical hydrogen production. Based on this concept, a photovoltaic-electrolysis-methane-steam-reforming (PV-E-MSR) hybrid system for efficient and low-carbon hydrogen production is designed and analyzed. In the hybrid system, middle-wavelength ( x -870 nm) sunlight is concentrated onto PV cells to generate electricity for water electrolysis and low-temperature heat (140 °C) for reactant preheating and vaporizing; the shorter- (280- x nm) and longer-wavelength (870–4000 nm) sunlight are concentrated onto MSR reactor to supply heat for MSR reaction. Thermodynamic analysis results show that solar-to-hydrogen efficiency and ratio of fossil-fuel energy in hydrogen of the hybrid system is higher to 54.6% and lower to 65.5%, respectively. Compared with a reference system composed of parallel-arranged solar MSR system and solar PV-E system, the hybrid system can generate 4.2% more hydrogen and save 3.8% fossil fuel, which benefits from full-spectrum optimized utilization of sunlight and complementarity between solar energy and fossil fuel. The concept and system proposed in this study might suggest a promising way for efficient and low-carbon hydrogen production from solar energy and fossil fuel.